A Brute-Force System for HID (Human Interface Device) Attack for Android Lock Screen Devices with Automatic Unlock Detection - Nunes, Mateus; Schneider, Rafael (Anais do Simpósio Brasileiro de Cibersegurança (SBSeg), 2023)
Electronic devices can be used to conduct illegal activities making examination of their contents essential for criminal investigation. Many mechanisms implemented over the years for securing users’ privacy can hinder lawful access to phone data. This research investigates attack via USB-OTG (On-the-Go) using HID (human interface device) and introduces a system for both PIN and pattern screen lock brute-force. Contributions include stop/resume attack and automatic unlock detection via sensor on display. An assessment was done with 18 compatible devices from real cases and found that 66% were compatible with password retrieval, most of them in less than one week.